The Role of Gamification in Software Development Lifecycle - Kalloniatis, Christos (IntechOpen, 2021)
Increasing user awareness in various information and communication technology (ICT) activities is one of the most challenging tasks for organizations. One popular way to engage users in various domains is gamification, which is the use of game elements and digital game design techniques in non-game applications. By using game elements, applications become more attractive and provide benefits such as increased user activity and sociability, quality, and productivity of actions. Gamification is introduced in various stages of the software development lifecycle starting with the first phase of eliciting requirements to the final phases of testing and evaluation of the system to be. In parallel, the introduction of game elements in non-games raises a number of security and privacy issues. This book presents innovative research efforts and technical solutions related to gamification and improving user engagement in all stages of the development process.